Medullary thyroid cancer outcomes in patients with undetectable versus normalized postoperative calcitonin levels. Issue 9 (26th April 2021) - Fanget, F; Demarchi, M S; Maillard, L; Lintis, A; Decaussin, M; Lifante, J C
Abstract: Background: Calcitonin (Ct) is a sensitive diagnostic biomarker and one of the most important prognostic factors in medullary thyroid cancer (MTC). This study aimed to evaluate progression-free survival and recurrence rates of MTC associated with undetectable compared with normalized serum Ct levels after surgery. Methods: This retrospective observational study included patients operated for MTC at the Digestive and Endocrine Surgery Department of Lyon Sud Hospital Centre between 2000 and 2019. Clinical and pathological factors were correlated with postoperative Ct concentrations. Undetectable and normalized Ct concentrations were defined as below 2 pg/ml and 2–10 pg/ml respectively. Results: Overall, 176 patients were treated for MTC, and 127 were considered biochemically cured after surgery. Of these, 24 and 103 had normalized and undetectable Ct concentrations respectively. Patients with Ct level normalization had a 25 per cent risk of disease recurrence, compared with 3 per cent in patients with undetectable Ct levels after surgery. The presence of metastasis in two or more compartments was predictive of failure to achieve undetectable Ct concentrations after surgery and an increased risk of recurrence. Conclusion: Among patients with biochemically cured MTC, those with undetectable or normalized Ct concentrations after surgery had different risks of recurrence. Simply assessing postoperative Ct normalization can be falsely reassuring, and long-term follow-up is needed. Lay summary: Calcitonin (Ct) is a sensitive diagnostic biomarker and one of the most important prognostic factors for medullary thyroid cancer outcomes; however, the significance of postoperative Ct levels remains controversial. This study evaluated the differences between normal and undetectable postoperative Ct levels in patients who had undergone surgical treatment for medullary thyroid cancer. Patients who experienced postoperative Ct level normalization had a higher risk of disease recurrence than those with undetectable Ct levels after surgery. Abstract : This study evaluated differences between normal and undetectable postoperative calcitonin (Ct) levels in patients who had undergone surgical treatment for medullary thyroid cancer. Patients who experienced postoperative Ct level normalization had a higher risk of disease recurrence than those with undetectable Ct levels.